Pattern of Lymphadenopathy on Fine Needle Aspiration Cytology in a Tertiary Level Hospital in Kathmandu - Shrestha, Amar Narayan; Kunwar, Shova; Aryal, Barun Babu; Adhikari, Anurag; Poudel, Ayusha (Nepalese Medical Journal, 2018)
Introduction: Fine Needle Aspiration Cytology is a relatively simple, inexpensive and rapid diagnostic procedure for identifying cause of lymphadenopathy without need for surgical procedures. This study aims to explain the pattern of lymphadenopathy seen on fine needle aspiration cytology in a tertiary level hospital in Kathmandu Materials and Methods: This study was conducted at Shree Birendra Hospital Nepal. Cases of lymph node FNAC done in the years 2073 and 2074 BS were included in the study. The cases were classified into reactive lymphadenitis, granulomatous lymphadenitis, tubercular lymphadenitis, lymphomas, leukemias, and metastases. Results: A total of 215 patients were included in the study, ranging in age from 2 to 84 years, out of which 98 were female and 117 were male. Reactive lymphadenitis was the most common diagnosis (n=126; 58.6%), followed by granulomatous lymphadenitis (n=34; 15.8%) and tubercular lymphadenitis (n=18; 8.4%). There were 18 cases of metastatic malignancies, 15 cases of suppurative lymphadenitis, and 2 cases of Hodgkin lymphoma and 2 cases of non-Hodgkin lymphoma. Conclusions: Reactive lymphadenitis is the most common type of lymphadenopathy encountered in FNAC, while in the elderly, metastases are more common.